Charles H. Lankester y el desarrollo histórico del Jardín Botánico Lankester: línea de tiempo y bibliografía anotada - Blanco, Mario A. (2023)
A timeline is presented with the main events in the life of Charles Herbert Lankester (1879–1969), underscoring his work as a naturalist and his scientific and horticultural interest in orchids and other plants, as well as the transformation of his property “El Silvestre” in the Lankester Botanical Garden of the University of Costa Rica (inaugurated in 1973) and its development through the last 50 years. The interactions between Charles Lankester and the Lankester Botanical Garden with many people and organizations are emphasized. Data on Lankester’s visit to Cocos Island in 1932–1933, which had not been mentioned in the botanical literature, are given. Some data are also presented on the first exhibitions of orchids and other plants in Costa Rica (including the very first orchid exhibition in the country in 1944) and on the selection process of Costa Rica’s national flower. An annotated bibliography is also given, chronologically organized, with more than 280 publications related to Charles Lankester (including 47 published by himself, some of them in Costa Rican newspapers and journals), to the Lankester Botanical Garden, and to people who had an important influence on its historical development.